Cognitive profile and mild cognitive impairment in people with chronic lower back pain - Corti, Emily; Gasson, Natalie; Loftus, Andrea (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
A growing body of evidence suggests Chronic Lower Back Pain (CLBP) is associated with cognitive dysfunction. Little is known, however, about the extent of cognitive impairment in CLBP. The present study explored the cognitive profile of people with CLBP and sought to determine the extent of Mild Cognitive Impairment (MCI) according to the DSM-V and the Movement Disorders Society criteria for MCI. Thirty-one participants with CLBP and 27 age and gender matched healthy controls completed a full neuropsychological battery, consisting of two tasks for each of the five cognitive domains (Executive Function, Attention/Working Memory, Memory, Language, and Visuospatial). Participants with CLBP performed worse, compared to controls, on measures of Attention/Working Memory, Memory, Language, and Visuospatial performance. Cognitive performance in CLBP was also compared to equivalent normative data to determine cognitive impairment. Sixteen CLBP participants were impaired on at least one cognitive measure, with 5 participants meeting criteria for MCI. MCI was not associated with pain-related experience, or psychological health. The present study supports and extends previous findings that CLBP is associated with cognitive dysfunction and some people with CLBP meet criteria for MCI. These findings support that rehabilitation in people with CLBP requires a multidisciplinary approach.